Sosio-cultural Education and its Impacts on the Society in Candirejo Tourism Village - Rahma, Anggi Jazilatur; Banowati, Eva; Sodiq, Ibnu (Universitas Negeri Semarang, 2024)
One of local tourist attractions is tourism village. The tourism community must have the roles as good and proper hosts for visitors. To achive this, it is necessary to have education that incorporates modeling in order to accomplish this goal. This can be accomplished through the provision of examples by educators or by other modeling activities such as comparative studies. This study aims to analyze the implementation, results of socio-cultural education, and its impact on the social and economic sectors of the Candirejo Tourist Village community. Qualitative method is used in this study. The results found that there are five types of sociocultural education: Seven Charms (Sapta Pesona), MSMEs (Micro, Small, and Medium Enterprises) or UMKM, social media, cultural markets, and foreign languages. The implementation of this education includes instilling values and modeling observed by participants. The results of the education indicate that tourist actors have exhibited positive behavioral changes as a result of the education. The existence of this tourism village has a positive impact on the social and economic fields, as evidenced by the maintained behavior of the community that aligns with local values, the presence of alternative income and employment for the community.